Microalgal starch: regulation of its quantity and roles - Pancha, Imran; Imamura, Sousuke (Frontiers in Plant Science, 2026)
Algae are important organisms that fix atmospheric carbon dioxide and produce organic compounds via photosynthesis. Among these, starch serves as the principal storage polysaccharide in algae and plays a crucial role in the production of various industrially relevant bioproducts, such as biofuels, animal feed, and bioplastics. This review article summarizes the functions of starch in microalgae and the impact of environmental factors, such as light and nutrient supply, on starch accumulation. Furthermore, it explores how microalgae regulate starch accumulation under specific conditions and introduces recent studies on the signaling pathways and related protein functions involved. Based on these insights, this review article discusses the future research challenges that need to be addressed. Such fundamental research findings form the foundation for applied research aimed at sustainable resource utilization, and are expected to provide crucial insights that will drive innovation in next-generation biotechnology.